Therapy-associated myelodysplastic syndrome with monosomy 7 arising in a Muir-Torre Syndrome patient carrying SETBP1 mutation - Ullman, David (Mol Clin Oncol, 2018)
Muir-Torre Syndrome (MTS) is a rare hereditary autosomal dominant cancer syndrome and is linked to hereditary non-polyposis colorectal carcinoma (Lynch Syndrome). Individuals develop various skin neoplasms in addition to colorectal, endometrial and upper gastrointestinal malignancies. Therapy-associated myelodysplastic syndrome (T-MDS) is an aggressive hematologic malignancy and is considered a pre-leukemic phase. T-MDS is associated with prior exposure to chemo- and radiotherapy that potentially results in DNA damage. The current case report presents a 74-year-old male MTS patient with prior history of solid tumors and radiation therapy with new onset cytopenia. A subsequent bone marrow biopsy revealed multilineage dysplasia with a high blast count and a diagnosis of high grade T-MDS was rendered. FISH and G-banded karyotype analyses revealed 5q deletion and monosomy 7. This is a unique case of T-MDS arising in the setting of MTS. Secondary malignancies including MDS and acute leukemia may occur in cancer survivors and are often associated with an unfavorable prognosis. This case demonstrates the need to be aware of the risk of secondary hematologic malignancies in cancer patients and a thorough clinical and lab work-up are warranted in patients with persistent or transfusion requiring cytopenia(s).